ANALISIS KEUANGAN (STUDI KASUS DI INDUSTRI PENGOLAHAN COKELAT BUMDes â€œMOTOTOMPIAANâ€ DESA POYUYANAN KECAMATAN PASSI BARAT KABUPATEN BOLAANG MONGONDOW) - Rahmawati Alhabsyi; Paulus A. Pangemanan; Eyverson Ruauw (COCOS, 2015)
ABSTRACT Financial statement analysis method to determine the performance of companies in a particular period. One of the methods of analysis used are ratio analysis. The analysis reveals the ratio of the elements in the financial statements. Figures from this analysis can show the activity of the company in the state is profitable or not. To measure the final results of the operation of a company can use the profitability ratio, of the value of this ratio can be in the know the strengths and weaknesses which is owned by businessman (businessman). The ratio may provide an indication of whether the company has sufficient cash to liabilities finasialnya or not enough. The purpose of this study was to determine the financial condition of the industry by using the Ratio Profitability and profitability of the chocolate manufacturing industry BUMDes "Mototompiaan". Profitability Ratio of Gross profit margin measurement results show that in the year 2013 and 2014 hasilnnya above the industry average. This means that the company is in good condition. But for the measurement results Net profit margins, ROI and ROE, shows that in the year 2013 and 2014 results are below the industry average. This means that the industry is not effective in getting benefits because the production process is only dependent on demand or production is not continuous or financial condition of the state is not good. Keywords : Analysis Of The Financial, Ratio Profitabiliy